Uma Proposta de Utilização da Transformada de Wavelet e Redes Neurais para Detecção de Ataques em Redes Ad Hoc Sem Fio - Ferreira, Ed’Wilson Tavares; Oliveira, Ruy de; Carrijo, Gilberto Arantes; Araújo, Nelcileno Virgílio de Souza (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2008: Companion Proceedings of the 8th Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2008.20902, 2008)
This article does not have an abstract.